Pelatihan Deteksi Dini Tumbuh Kembang Anak Bagi Guru Tk/Ra Se-Kota Kendari - Salwiah; Abubakar, Sitti Rahmaniar; Saranani, Muhamad Safiuddin; Asmuddin; Hidayat, Ahid; Gadafi, Muamal; Hidayah, Afifah Nur; Mustar, Sri Yuliani (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
This Community Service Program is entitled "Early Detection Training for Child Growth and Development for Kindergarten/RA Teachers in Kendari City." The purpose of this service activity is to provide knowledge and insight for kindergarten/RA teachers related to the detection of child growth and development that can be implemented in schools. The specific targets to be achieved from the implementation of this community service activity are as follows, namely: (a) the existence of teachers' knowledge and skills in assessing the nutritional status of early childhood, (b) teachers can find out how to carry out early detection of developmental deviations using KPSP, (c) teachers can detect children's growth such as measuring the child's head circumference, height and testing early childhood hearing and vision,  and (d) the creation of more effective communication with parents related to child growth and development. The methods used in the implementation of this activity are as follows; (1) Preparation Stage. Where the community service team digs information about training needs, determines training materials and participants and prepares materials and tools used for early detection of child growth and development training activities for kindergarten/RA teachers. (2) Implementation Stage. The community service team provides an initial test first to find out the initial knowledge of the trainees, then the community service team provides education about early detection of child growth and development and conducts a simulation of child growth and development detection. (3) Evaluation and Reporting Stage. The community service team conducted an evaluation related to the knowledge and understanding of kindergarten/RA teachers related to the detection of early childhood growth and development.